2019
DOI: 10.3390/antibiotics8030103
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Action of Phage and Antibiotics: Parameters to Enhance the Killing Efficacy Against Mono and Dual-Species Biofilms

Abstract: Pseudomonas aeruginosa and Staphylococcus aureus are opportunistic pathogens and are commonly found in polymicrobial biofilm-associated diseases, namely chronic wounds. Their co-existence in a biofilm contributes to an increased tolerance of the biofilm to antibiotics. Combined treatments of bacteriophages and antibiotics have shown a promising antibiofilm activity, due to the profound differences in their mechanisms of action. In this study, 48 h old mono and dual-species biofilms were treated with a newly is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
112
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(122 citation statements)
references
References 54 publications
9
112
0
1
Order By: Relevance
“…Our results support the combined use of phage and antibiotics to provide synergistic efficacy in treating bacterial infections, as reported by others (Oechslin et al, 2016;Ronayne et al, 2016;Wang et al, 2017). The combination of phage and antibiotics can also act synergistically to reduce bacterial density in biofilms (Akturk et al, 2019). A recent study reported that while the phage had a small effect on pathogen density on its own, it considerably increased the sensitivity of Ralstonia solanacearum to antibiotics produced by Bacillus amyloliquefaciens (Wang et al, 2017).…”
Section: Discussionsupporting
confidence: 89%
“…Our results support the combined use of phage and antibiotics to provide synergistic efficacy in treating bacterial infections, as reported by others (Oechslin et al, 2016;Ronayne et al, 2016;Wang et al, 2017). The combination of phage and antibiotics can also act synergistically to reduce bacterial density in biofilms (Akturk et al, 2019). A recent study reported that while the phage had a small effect on pathogen density on its own, it considerably increased the sensitivity of Ralstonia solanacearum to antibiotics produced by Bacillus amyloliquefaciens (Wang et al, 2017).…”
Section: Discussionsupporting
confidence: 89%
“…For example, one of our main results states that phage-antibiotic combined therapy has a greater antimicrobial effect than single phage or antibiotic therapies, this is consistent with several in vitro settings that show a greater bacterial density reduction for combined rather than sin-gle therapies [25][26][27][28] . Moreover, additional studies explore the use of sub-lethal concentrations of antibiotics otherwise insufficient for controlling bacterial growth but efficient when combined with phage against diverse bacterial populations 25,26,28,29 . These findings are consistent with our in silico outcomes where pathogen clearance is observed at sub-MIC antibiotic levels in the combined therapy framework.…”
Section: Discussionsupporting
confidence: 88%
“…If so, this additional synergy may help to resolve the resistance problem and also guide use of sub-MIC concentrations of antibiotics. Besides reducing toxic side effects associated with high concentrations of antibiotics, sub-MIC concentrations can improve phage infectivity through morphological changes of the bacterial cell 9, 35,36 or by not interfering with the phage replication cycle 25,26 . When combined in an immunocompetent context, we find that phage-antibiotic combination therapy is robust to quantitatively and qualitatively distinct resistance profiles.…”
Section: Discussionmentioning
confidence: 99%
“…Ф HP3, used in this study, encodes two subunits of DNA topoisomerase II (data not shown), suggesting that ciprofloxacin inhibits both the bacterial and the phage topoisomerases. Similarly, recent biofilm PAS studies noted that sequentially treating cells with phage and ciprofloxacin (noted synergism) instead of a simultaneous application (noted antagonism), may have allowed phage replication to occur first before ciprofloxacin's interruption (23,38). These results raise the possibility that the type of interactions in each phage-antibiotic combination is heavily dictated by the primary target of the antibiotic and the cellular processes required for phage replication (34,39,40).…”
Section: The Class Of Antibiotic Determines the Type Of Interaction Wmentioning
confidence: 94%
“…For instance, quinolones can be synergistic with phages against P. aeruginosa in one study while antagonistic in another (21,22). Sometimes, there are even two types of interactions found with the same antibiotic when they are combined with phages (23). Moreover, phage-antibiotic synergy (PAS) is usually studied with only one or two concentrations of the antimicrobials, which are wholly insufficient in predicting combinatorial concentrations that are efficacious during treatment.…”
Section: Five Years Later In 2019 the Centers For Disease Control Anmentioning
confidence: 99%